Biosynthesis of vanillic acid by Ochrobactrum anthropi and its applications. (15th October 2022) - Girawale, Savita D.; Meena, Surya N.; Nandre, Vinod S.; Waghmode, Suresh B.; Kodam, Kisan M.
Graphical abstract: Abstract: Vanillic acid has always been in high-demand in pharmaceutical, cosmetic, food, flavor, alcohol and polymer industries. Present study achieved highly pure synthesis of vanillic acid from vanillin using whole cells of Ochrobactrum anthropi strain T5_1. The complete biotransformation of vanillin (2 g/L) in to vanillic acid (2.2 g/L) with 95 % yield was achieved in single step in 7 h, whereas 5 g/L vanillin was converted to vanillic acid in 31 h. The vanillic acid thus produced was validated using LC-MS, GC–MS, FTIR and NMR. Further, vanillic acid was evaluated for in vitro anti-tyrosinase and cytotoxic properties on B16F1 skin cell line in dose dependent manner with IC50 values of 15.84 mM and 9.24 mM respectively. The in silico Swiss target study predicted carbonic acid anhydrase IX and XII as key targets of vanillic acid inside the B16F1 skin cell line and revealed the possible mechanism underlying cell toxicity. Molecular docking indicated a strong linkage between vanillic acid and tyrosinase through four hydrogen and several hydrophobic bonds, with ΔG of −3.36 kJ/mol and Ki of 3.46 mM. The bioavailability of vanillic acid was confirmed by the Swiss ADME study with no violation of Lipinski's five rules.